The Comparison of Group Versus Individual Format of Cognitive-Behavior Therapy on Fear of Positive Evaluation - Ebrahim Rezaei-Dogaheh; Parvaneh Mohammadkhani; Behrouz Dolatshahi (University of Social Welfare and Rehabilitation Sciences, 2012)
Objective: This study aimed to compare the effectiveness of cognitive-behavior group therapy (CBGT) and individual cognitive -behavior therapy (ICBT) in reducing fear of positive evaluation in social anxiety disorder (SAD). Material & Methods: The subjects included 28 patients referred to psychological treatment centers of University of Social Welfare and Rehabilitation Sciences who diagnosed with SAD. The sample randomly allocated in two groups of 14 participants. Each groups participated in 12 sessions mainly based on Heimberg's model for SAD. Pretest and posttest data using Fear of Positive Evaluation Scale (FPES), Social Phobia Inventory (SPIN) and the Beck Depression Inventory - Second Edition (BDI-II) were collected and analyzed with analysis of covariance. Results: When pretest depression was co varied out, CBGT compared with ICBT was equally effective in reducing fear of positive evaluation and there was no significant difference between two groups in FPES scores after treatment. In addition, improve rates of CBGT group was not significantly higher than ICBT. Conclusion: The clinical significance of findings by different criteria indicated the equality of effectiveness of the two formats.